INCIDENT OF COMPETENCE DISPLACEMENT: LINEAMENTS OF A GUARANTEE AGAINST SERIOUS VIOLATIONS OF HUMAN RIGHTS - Steinmetz, Wilson Antônio (Unoesc International Legal Seminar, 2017)
The objective is to analyze the removal to the jurisdiction of the Federal Courts in cases of severe violation of human rights according to the interpretation of the Superior Court of Justice.